2013
DOI: 10.1186/bcr3521
|View full text |Cite
|
Sign up to set email alerts
|

PB.21: Relationship between volumetric breast density and socioeconomic status

Abstract: West of Scotland Breast Screening Centre, Glasgow, UK; 2 Scottish Breast Screening Programme, UK Breast Cancer Research 2013, 15(Suppl 1):O3 Introduction: Women with B5a (non-invasive) preoperative core biopsies upgraded to invasive disease at surgery have a high chance of needing further surgery. The average B5a upgrade rate across UK breast screening programmes is around 20%. Through this Scottish review, we aim to identify factors affecting upgrade rates and ways to improve our performance. Methods: This wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…To get more insight into the geographic differences, we further studied SES and urbanisation. A (weak) positive association between SES and breast density has been observed before [ 7 , 9 , 11 ]. Despite the differences in setting (e.g., country) and definitions (both SES and density), these results appear to be consistent with our observations.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…To get more insight into the geographic differences, we further studied SES and urbanisation. A (weak) positive association between SES and breast density has been observed before [ 7 , 9 , 11 ]. Despite the differences in setting (e.g., country) and definitions (both SES and density), these results appear to be consistent with our observations.…”
Section: Discussionmentioning
confidence: 86%
“…As part of the DENSE trial, the volumetric breast density distribution could be determined using unprocessed mammogram data collected from screening units throughout the country [ 6 ]. Although this is, to our knowledge, the first study to address the geographic variation in volumetric breast density within a national screening programme, a few studies have reported on the association of geographic (e.g., urbanisation level) and demographic (e.g., socio-economic status [SES]) characteristics with breast density [ 7 11 ]. These factors may help clarify differences between screening areas, but the previous results have been somewhat inconsistent.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation